Comparison between the Administration of Betel Leaves (Piper Betle L.) and Binahong Leaf (Anredera Cordifolia) on Flour Albus in Women of Reliable Age in Serua Ciputat Regional Region in 2022 - Lilis Kurniati; Bunga Tiara Carolin; Nurul Husnul Lail (KHD-Production, 2022)
Background: In Indonesia, women who have experienced vaginal discharge are very high as much as 75%, of which 50% occur in adolescents and 25% occur in women of childbearing age (WUS). Vaginal discharge is discharge except for blood from the vaginal canal, whether smelly or not, accompanied by itching around it. Objective: Knowing the Comparison Between Decoction of Betel Leaves (Piper Betle L) and Binahong Leaves (Anredera cordifolia) against vaginal discharge in women of childbearing age in Serua Ciputat Village in 2022. Methodology: this quasi-experimental research using a two group pre-test and post-test design. The population in this study were women of childbearing age who were married in the Serua Ciputat Village, South Tangerang City, totaling 30 respondents. ) for the incidence of flour albus. Results: The results of the univariate analysis mean that the pretest of betel leaf decoction is 14.93 and the posttest average value is 7.80, while the pretest average of binahong leaf decoction is 14.80 and the posttest average value is 8.33. Conclusions: Based on the research that has been done on the comparison between giving betel leaf decoction (Piper Betle L) and Binahong leaf (Anredera cordifolia), it can be concluded that there is no difference in the effect before and after administration of betel leaf stew and binahong leaf decoction on vaginal discharge in women of childbearing age. in the village area of ​​Serua Suggestions: Hopefully the results of this study can provide information about fluor albus and make green betel leaf boiled water and binahong leaf stew as alternatives that can be used to prevent the occurrence of fluor albus. Keywords: Vaginal discharge, Women of Childbearing Age (WUS), Betel Leaf, Leaf Binahong.